2021
DOI: 10.1177/10634266211051404
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Self-Regulation: A Comparison of Goals and Self-Monitoring for High School Students With Disabilities

Abstract: High school students, particularly those with disabilities, often struggle with academic engagement in general education classes. One empirically supported method for improving academic engagement includes self-regulation interventions. However, individual effects of frequently used self-regulation strategies’ goal setting and self-monitoring remain unknown. To address this issue, we implemented a multiple-probe single-case design with embedded alternating treatments to evaluate the differential impact of beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The measurement of self-regulation in the overall subjects used Self Control Rating Scale (SCRS) to consider that the scale could reveal impulsivity and self-regulation. Self-control and self-regulation refer to the same variable: an individual's capacity to control their impulsive behavior and divert it to more appropriate behavior (Baumeister, 2002;Estrapala et al, 2021). Self-control has defined the ability to rule out temptation or impulsive behavior to perform a more appropriate task.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of self-regulation in the overall subjects used Self Control Rating Scale (SCRS) to consider that the scale could reveal impulsivity and self-regulation. Self-control and self-regulation refer to the same variable: an individual's capacity to control their impulsive behavior and divert it to more appropriate behavior (Baumeister, 2002;Estrapala et al, 2021). Self-control has defined the ability to rule out temptation or impulsive behavior to perform a more appropriate task.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers could meet with students individually and help them set personal goals and teach them how to self-monitor their performance. Estrapala et al (2021) reported that goal-setting is a socially-valid intervention for students with EBD.…”
Section: Implementing Mindfulness In the Classroommentioning
confidence: 99%
“…However, most behavioral self-regulation interventions tend to be adult rather than self-directed (Estrapala et al, 2021), which limits the opportunities for students to practice informed decision-making, problem-solving, and self-advocacy (Korinek, 2015). Including students with internalizing behaviors in intervention decisions is important because teachers and other interventionists are unaware of (a) environmental triggers that might exacerbate certain behaviors and (b) unobservable internalizing thoughts and emotions that possibly contribute to problem behaviors.…”
Section: Self-regulationmentioning
confidence: 99%
“…“Most behavioral self-regulation interventions tend to be adult rather than self-directed (Estrapala et al, 2021), which limits the opportunities for students to practice informed decision-making, problem-solving, and self-advocacy (Korinek, 2015). …”
Section: Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation